PROSES INTERAKSI KOMUNIKASI SISWA SMP DALAM DISKUSI KELOMPOK MATERI PERSAMAAN GARIS LURUS DITINJAU DARI JENIS KELAMIN - Moh Syukron Maftuh (INSPIRAMATIKA, 2020)
This research aims to describe the process of communication interaction within group discussion based on gender in Mathematics’ study particularly straight-line equations. The research was carried out at 8th grade in SMP Negeri 1 Driyorejo The research involves two kind of subject namely the women's group and the men's group which each group consisted of three students and is a descriptive study with a qualitative approach. There are three stages in collecting students’ data: interview before the class started, record each conversation during the group discussion, and interview after the learning process. In terms of validity of the research, those data are checked using time triangulation. The results show that women’s group are more active during discussion compare with man’s group. While all member in women’s group communicated actively in solving problem, some of men’s member contributed in solving problem in worksheet